Genetic Variability, Correlation and Path Analysis in Rice (Oryza sativa L.) under Coastal Salinity Conditions of Goa - MANOHARA, K. K.; SINGH, NARENDRA PRATAP (Journal of the Indian Society of Coastal Agricultural Research, 2023)
An experiment was conducted during wet season of 2012 to study genetic variability, correlation and path coefficient analysis in 31 diverse salt tolerant rice genotypes under coastal salinity conditions of Goa. Analysis of variance showed highly significant differences among the tested genotypes for all the characters studied. Phenotypic coefficient of variation (PCV) was higher compared to that of genotypic coefficient of variation (GCV) in all the characters indicating the influence of environment on the expression of these traits. High heritability coupled with high genetic advance was observed for days to 50% flowering, length to breadth ratio, 100 grain weight, straw yield per plot, harvest index and grain yield per plot indicating that these characters are governed by additive gene action. Grain yield per plot showed positive and significant correlation with panicle length, grain length, filled grains per panicle, spikelet fertility and straw yield per plot and harvest index. Results of the path analysis indicated that grain length had maximum direct effect on grain yield followed by harvest index and straw yield per plot. Such characters could be utilized in selection for improving the grain yield under coastal salinity conditions.